2019
DOI: 10.1021/acs.molpharmaceut.9b00737
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastable and Biofunctionalizable Conjugated Polymer Nanoparticles with Encapsulated Iron for Ferroptosis Assisted Chemodynamic Therapy

Abstract: We report the development of novel tumor-targeted conjugated polymer nanoparticles (CPNPs) carrying iron for chemodynamic therapy (CDT). Tumor cell killing proceeds through ferroptosis, a reactive oxygen species (ROS) mechanism that is not dependent on external activation by, for example, light, as is the case in photodynamic therapy (PDT). The ferroptosis mechanism is also not heavily reliant on oxygen availability and is, therefore, promising for the treatment of hypoxic tumors. In this work, we apply this d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 112 publications
0
27
0
Order By: Relevance
“…NPs can incorporate molecules on their surface that preferentially target cancer cells (i.e., folate [232] and 5-(4-hydroxyphenyl)-10,15,20-triphenylporphyrin [233]). The successful delivery of anticancer drugs can be achieved through this strategy [234][235][236][237].…”
Section: The Future Of Nanoparticles (Np) For Cancer Targeting and Timentioning
confidence: 99%
See 2 more Smart Citations
“…NPs can incorporate molecules on their surface that preferentially target cancer cells (i.e., folate [232] and 5-(4-hydroxyphenyl)-10,15,20-triphenylporphyrin [233]). The successful delivery of anticancer drugs can be achieved through this strategy [234][235][236][237].…”
Section: The Future Of Nanoparticles (Np) For Cancer Targeting and Timentioning
confidence: 99%
“…Some recent advances have been made regarding the synthesis of NPs loaded with metals, mainly with iron, which can facilitate lipid peroxidation in cancer cells [234,238,239]. As previously indicated, iron overload produces an increase in random peroxidation products that is entirely unspecific and could lead to harmful oxidative stress in non-cancer cells.…”
Section: The Future Of Nanoparticles (Np) For Cancer Targeting and Timentioning
confidence: 99%
See 1 more Smart Citation
“…PDT combined with the Fenton reaction[ 176 ] is a feasible treatment method for CSCs showing strong drug resistance. In addition, a new type of programmed cell death, ferroptosis, is also closely related to Fe 2+ and the Fenton reaction[ 177 ]. Some researchers have found that ferricin chelates lysosomal iron[ 178 ].…”
Section: Impact Of Ros From Pdt On Cscsmentioning
confidence: 99%
“…In recent years, an effort has been made to develop nanoparticles with encapsulated iron for ferroptosis assisted CDT. Conjugated polymer nanoparticles (CPNPs) containing iron(III) and targeted to endothelin-B receptors selectively trigger ferroptosis of melanoma cells with no significant effect on normal cells [63]. Wang and colleagues developed redox-and light-responsive (RLR) nanoparticles that contained iron and were programmed to degrade and self-activate in an acidic environment with excessive glutathione, as is the case for a tumor microenvironment (TME).…”
Section: Iron-containing Nanoparticles In Oncotherapymentioning
confidence: 99%